Comparison of practicability and effectiveness between unassisted HIV self-testing and directly assisted HIV self-testing in the Democratic Republic of the Congo: a randomized feasibility trial - Serge Tonen-Wolyec; Charles Kayembe Tshilumba; Salomon Batina-Agasa; Roland Marini Djang’eing’a; Marie-Pierre Hayette; Laurent Belec (BMC Infectious Diseases, 2020)
Abstract Background HIV self-testing (HIVST) can be performed using directly assisted and unassisted approaches in facilities or communities to reach different populations. The aim of this study was to compare the practicability and effectiveness of the two delivery approaches for HIVST, unassisted HIVST (UH) and directly assisted HIVST (DAH), in the field setting of Kisangani, the Democratic Republic of the Congo (DRC). Methods A randomized (1:1), non-blinded, non-inferiority trial using a blood-based and facility-based HIVST method was carried out in four facilities in Kisangani, the DRC, targeting populations at high risk for HIV infection. The primary outcome was the difference in the practicability of the HIV self-test between the two arms. Practicability was defined as successfully performing the test and correctly interpreting the result. Requests for assistance, positivity rate, linkage to care, and willingness to buy an HIV self-test kit constituted the secondary outcomes for HIVST effectiveness. The adjusted risk ratios (aRRs) were calculated using Poisson regression. Results The rate of successfully performing the test was same (93.2%) in the UH and DAH arms. The rate of correctly interpreting the results was 86.9% in the UH arm versus 93.2% in the DAH arm, for a difference of − 6.3%. After the follow-up 72 h later, participants in the UH arm had a significantly lower chance of correctly interpreting the test results than those in the DAH arm (aRR: 0.60; P = 0.019). Although the positivity rate was 3.4% among the participants in the DAH arm and 1.7% among those in the UH arm, no significant differences were found between the two arms in the positivity rate, requests for assistance, and linkage to care. Willingness to buy an HIV self-test was higher in the UH arm than in the DAH arm (92.3% versus 74.1%; aRR: 4.20; P < 0.001). Conclusion The results of this study indicate that UH is as practicable and effective as DAH among individuals at high risk for HIV infection in Kisangani, the DRC. However, additional support tools need to be assessed to improve the interpretation of the self-test results when using the UH approach. Trial registration PACTR201904546865585. Registered 03 April 2019 - Retrospectively registered, https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=6032